Evaluation of Family Burden and Quality of Life of Parents with Children with Disability. - Çolak, Bahar; Kahriman, İlknur (American Journal of Family Therapy)
This research was conducted to determine the family burden and quality of life of parents with children with disabilities. This descriptive study was carried out within special education and rehabilitation centers between the dates of October, 2017 and July, 2018. The sample of the study consisted of 518 parents. Data regarding the study were collected using the "Family Burden Assessment Scale" and "WHOQOL-BREF-TR Scale". A negative moderate and significant relationship has been detected between the physical domain and FBAS scores of the parents subjected while a negative strong and significant relationship was detected in the spiritual, social and environmental domains. It has been concluded that the quality of life has decreased as the family burden of the parents increased. In addition, family burden of parents had a negative effect on their quality of life.